The Implementation of Project-Based Learning in Translation Class of English Literature Undergraduate Program at the University of Bina Sarana Informatika - Yuskar, Bobby Octavia; Lustyantie, Ninuk; Murthadho, Fathyati (Bulletin of Science Education, 2024)
This research focuses on teaching translation using Project-Based Learning with eight translation methods in translation class of the English Literature Undergraduate Program at the University of Bina Sarana Informatika (UBSI). The subjects of this research are sixteen students. The research method used is qualitative. The translation methods used are eight translation methods introduced by Newmark. The teaching method used is Project-Based Learning (PBL). PBL is chosen because it exploits innovative learning that emphasizes contextual learning through activities that challenge students’ critical thinking patterns. The main material for this translation project is a number of articles that highlight local and global issues downloaded from the Jakarta Post newspaper website. The translation carried out is the process of translating several texts from English as the Source Language (SL) into Indonesian as the Target Language (TL). The translation process is carried out individually within a time limit set by the Researcher as the Facilitator. Translation research is conducted by applying an accuracy assessment instrument designed by Nababan covering three main aspects: Accuracy Aspect, Acceptability Aspect and Readibility Aspect. Keywords: Learning Translation, Project-Based Learning